Implementation of ICT learning at SDN Pancasila Lembang - Alvyn Hadrian Nugraha (Hipkin Journal of Educational Research, 2025)
The rapid development of Information and Communication Technology (ICT) requires the education sector to adapt, particularly in the implementation of learning in elementary schools. This study aims to describe the implementation of ICT learning at SDN Pancasila, focusing on curriculum implementation, teacher competence, instructional delivery, and available facilities and infrastructure. This study employs a qualitative approach, using observation methods and semi-structured interviews with ICT teachers. The study's results indicate that the implementation of the Kurikulum Merdeka provides schools with the flexibility to determine ICT learning materials and methods in accordance with students' needs. Teachers have basic competencies in using ICT but are not yet fully effective in integrating digital-based learning. The implementation of ICT learning went quite well, even though they still faced limited facilities such as computers and laptops. Students showed a strong interest in ICT-based learning because it was perceived as more engaging and interactive. Improvement of teacher competence and equal distribution of ICT facilities are needed to support the implementation of more effective, efficient, and equitable learning in elementary schools, especially at SDN Pancasila Lembang.   Abstrak Perkembangan Teknologi Informasi dan Komunikasi (TIK) yang pesat menuntut dunia pendidikan untuk turut beradaptasi, khususnya dalam pelaksanaan pembelajaran di sekolah dasar. Penelitian ini bertujuan untuk mendeskripsikan implementasi pembelajaran TIK di SDN Pancasila ditinjau dari aspek penerapan kurikulum, kompetensi guru, pelaksanaan pembelajaran, serta sarana dan prasarana yang tersedia. Penelitian ini menggunakan pendekatan kualitatif dengan metode observasi dan wawancara semi-terstruktur terhadap guru TIK. Hasil penelitian menunjukkan bahwa penerapan Kurikulum Merdeka memberikan keleluasaan bagi sekolah dalam menentukan materi dan metode pembelajaran TIK sesuai kebutuhan murid. Guru memiliki kompetensi dasar dalam memanfaatkan TIK, namun belum optimal dalam integrasi pembelajaran berbasis digital. Pelaksanaan pembelajaran TIK berlangsung cukup baik meskipun masih menghadapi keterbatasan fasilitas seperti komputer dan laptop. Murid menunjukkan minat yang tinggi terhadap pembelajaran berbasis TIK karena dianggap lebih menarik dan interaktif. Diperlukan peningkatan kompetensi guru dan pemerataan fasilitas TIK guna mendukung pelaksanaan pembelajaran yang lebih efektif, efisien dan merata di sekolah dasar yang utamanya di SDN Pancasila Lembang. Kata Kunci: Kurikulum Merdeka; pembelajaran TIK; teknologi informasi dan komunikasi